Tamanho populacional de lobos-guará (Chrysocyon brachyurus) em uma área protegida de cerrado no sudeste do Brasil - Ramalho, Fernanda do Passo (2011)
The Maned Wolf (Chrysocyon brachyurus) is listed among the threatened extinction species in Brazil due to loss of its natural habitat to agriculture and frequent roadkill. Aiming to determinate the population size of C. brachyurus into a Ecological Station in the northeast of Sao Paulo State (Estação Ecológica do Jataí EEJ), a non invasive method genetic analysis of feces was employed to confirm the specie findings which deposit the feces, in accordance of morphological characteristics and specific scent of the C. brachyurus specie. Through a panel of five loci microsatellite was possible to identify each collected sample. Among the 41 stool samples, we identified 13 specimens of C. brachyurus in the EEJ. The probability of identity (PID) was 0.8 x 10 -6 and the probability of not detecting allelic (allelic dropout) was 16.2%. There was no imbalance linkage between the analyzed loci. Values for C. brachyurus internal heterozygosity were rated low. The observed heterozygosity (Ho) average was 0.52 and expected heterozygosity (He) average was 0.72. The number of alleles per locus was found to be 5.4. In the analysis of Hardy-Weinberg were found three loci that showed some deviations, after Bonferroni correction: loci 2018, 2054 and 2140. Fis values were highly significant for all into the situ population. The degree of relatedness of individuals, or varied of 0.000 (not relative) to 0.5253 (father and son), indicating that there are related animals in the area. Tests conducted to determine the gender of the samples of C. brachyurus were not found satisfactory results, once the expected fragments were not amplified in any of the tests and in none of the samples. The estimation of the population size of the C. brachyurus in the area of EEJ may be used as reference of management action plans of species conservation.